2022
DOI: 10.1093/mnras/stac118
|View full text |Cite
|
Sign up to set email alerts
|

FGC 1287 and its enigmatic 250 kpc long HI tail in the outskirts of Abell 1367

Abstract: We present H i and radio continuum, narrow–band Hα imaging, IFU spectroscopy, and X–ray observations of the FGC 1287 triplet projected ∼ 1.8 Mpc west of the galaxy cluster Abell 1367. One triplet member, FGC 1287, displays an exceptionally long, 250 kpc H i tail and an unperturbed stellar disk which are the typical signatures of ram pressure stripping (RPS). To generate detectable RPS signatures the presence of an Intra–cluster medium ICM/intra–group medium IGM with sufficient density to produce RPS at a reali… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…As a closing remark for this discussion we also note that despite the apparently simple requirement for ram pressure stripping (i.e., sufficient ram pressure to overcome the gravitational attraction of the gas disk) and extensive efforts to simulate this process in increasing detail, there remain systems that are challenging to explain. In particular, the recent discovery of an enormous (apparently) ram-pressure-stripped H I tail in a system outside of a cluster, where no significant intergalatic medium could be detected (Scott et al 2022), poses difficult questions regarding its origin and could even suggest that some BC-like objects might exist outside of clusters.…”
Section: Properties Of Ram Pressure Stripped Gas Clumps In Simulationsmentioning
confidence: 99%
“…As a closing remark for this discussion we also note that despite the apparently simple requirement for ram pressure stripping (i.e., sufficient ram pressure to overcome the gravitational attraction of the gas disk) and extensive efforts to simulate this process in increasing detail, there remain systems that are challenging to explain. In particular, the recent discovery of an enormous (apparently) ram-pressure-stripped H I tail in a system outside of a cluster, where no significant intergalatic medium could be detected (Scott et al 2022), poses difficult questions regarding its origin and could even suggest that some BC-like objects might exist outside of clusters.…”
Section: Properties Of Ram Pressure Stripped Gas Clumps In Simulationsmentioning
confidence: 99%
“…Long HI tails > ∼ 100 kpc are also seen in the galaxies NGC 4388 [192] and NGC 4424 in the Virgo cluster; a lower limit of the tail length is because of a limited flux sensitivity [193]. An example of an exceptionally long HI tail in the Virgo-500 kpc driven by ram pressure has been demonstrated by Koopmann et al [194], and another of length 250 kpc has been found recently in the outskirts of the Abell 1367 cluster [195]. In general, a 100 kpc length of ram pressure-driven tail does not seem to be an overestimate, both for Hα and HI tails [98,189,196].…”
Section: Tidal and Ram-pressure Strippingmentioning
confidence: 88%
“…Thus it is likely that a considerable fraction of present-day cluster galaxies have experienced morphological transformation in galaxy groups, which allow more violent mergers between galaxies (preprocessing; Zabludoff & Mulchaey 1998;De Lucia et al 2012). Recent observational and theoretical studies emphasize the importance of galaxy groups as the environments for preprocessing (Cortese et al 2006;Just et al 2019;Kleiner et al 2021;Scott et al 2022).…”
Section: Introductionmentioning
confidence: 99%